Schoolchildren's personal exposure to ultrafine particles in and near Accra, Ghana. (December 2019) - Nyarku, Mawutorli; Buonanno, Giorgio; Ofosu, Francis; Jayaratne, Rohan; Mazaheri, Mandana; Morawska, Lidia
Highlights: Information relating to personal UFP exposure in Ghana is lacking. We assessed the daily personal UFP exposure of schoolchildren in and near Accra. Exposure to UFPs in Accra was among the highest in the world. Emissions from cooking, combustion and traffic were the main sources of UFPs. Abstract: Exposure to air pollution is a significant health risk, and children who are exposed to it are likely to have lifelong consequences. Ultrafine particles (UFPs) are emitted by all combustion sources, and can be used as a proxy for the presence of combustion products. The present study, the first of its kind to be conducted in Africa, assessed schoolchildren's exposure to UFPs, and apportioned their daily exposure to seven different microenvironments that they inhabited on a typical school day. The personal exposure of 61 pupils attending three junior high schools was measured for 24 h each using wearable monitors over a period of 10 weeks. Two of the schools were located in suburbs of Accra and the third in Berekuso, a nearby rural community. The results of our study revealed the complex nature of children's UFP exposure and its overall high to very high levels, significantly influenced by the locality (suburb) of residence and the type of activities in which the children were engaged. The mean ( ± standard error) daily exposure to UFPs ( c m - 3 ) was 6.9 × 10 4 ( ± 6.8 × 10 3 ), 4.9 ( ± 1.0 ) × 10 4 and 1.6 × 10 4 ± 1.9 × 10 3 for pupils attending the Ashia Mills, Faith Baptist and Berekuso Basic Schools, respectively. Pupils attending the schools in urban Accra received higher exposure than those attending the school in the rural environment of Berekuso. The highest mean microenvironmental exposure was registered in the Home other microenvironment in an urban school and in Bedroom in another urban school and the rural school. The high exposure in Home other was due to pupils conducting trash burning and encountering environmental tobacco smoke, and the high exposure in Bedroom microenvironment was due to the burning of mosquito coils at night to prevent malaria. The principal sources that heightened exposure to UFPs were emissions from cooking (using firewood and charcoal), vehicular traffic and combustion of biomass and trash. All pupils recorded the highest exposure intensity in the Kitchen microenvironment.